Meridian Club records, - Meridian Club (Spokane, Wash.)
Records of the Meridian Club, a woman's club in Spokane. The collection primarily contains the minutes of the meetings, which include member's names and records of the club's activities. It also includes a small amount of correspondence, primarily with the Spokane Federation of Women's Clubs.